Technical and tactical effectiveness is related to time-motion performance in elite rugby - Ungureanu, A. N.; Brustio, P. R.; Lupo, C. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Performance during a rugby union game is based on technical and tactical performance and running activity. Notational and time-motion analyses may be useful to better understand the mutual influence of both factors. Thus, this study investigated the relationship between technical and tactical performance and running activity for both forwards and backs during official games of under-20 Six Nations Championship. METHODS: Technical and tactical performance and running activity of thirty under-20 elite players (age range: 18-20 years; total games = 98) were assessed in relation to 20 key performance indicators (KPIs) and analysed separately for forwards and backs. General linear mixed models were performed to evaluate the relationship between KPIs, including subjects and games as random effect. RESULTS: Different technical and tactical KPIs influenced the running activities for forwards and backs, while tackles, passes, and positive work rate influenced running activity (i.e. total distance, meters/minute, % high speed running, and explosive distance) in forwards. Only passes and possession influenced running activity (i.e. % high-speed running and distance covered above 14 km/h, 17 km/h, and 24 km/h speed) in backs. CONCLUSIONS: Technical and tactical performance affects running activities differently for forwards and backs. During training sessions, coaches should stimulate forwards to be more active (i.e. to complete more meters/minute, more explosive distance) and backs to control more the defensive structure (i.e. less % high-speed running and less distance covered above 14 km/h and 17 km/h speed). A progression from short to long game sequences, that quickly recreate the game plan and keep the momentum, could stimulate technical and tactical performance, as well as physical conditioning.